PROTECTION OF WAR REPORTERS IN ARMED CONFLICT AREAS BASED ON INTERNATIONAL LAW (CASE STUDY OF THE IRAQ AND SYRIA CONFLICT) - Desia Rakhma Banjarani; Sri Sulastuti; Kisti Artiasha (Cepalo, 2019)
The work of journalists in conflict zones to convey the facts of war objectively is often life-threatening. In several international treaties, provisions regarding the protection of journalists working in conflict areas have been included, but there are some obstacles to enforcing the provisions of these international agreements. The issue to be discussed in this research is how is the protection of journalists in armed conflict based on international treaties in humanitarian law? And what about criminal liability for offenders who violate humanitarian law (war) by "killing - persecuting" war journalists?This study uses a normative legal problem approach (library law research) with a descriptive analytical type of research. The data obtained are secondary data from sources such as literature, articles and internet sites. The results showed that the protection of journalists who served during conflicts in international law was regulated in the 1907 Hague Convention, 1949 Geneva Convention, Additional Protocol I of the 1977 Geneva Convention, and the Rome Statute. In the context of criminal responsibility for perpetrators of human rights violations against journalists in this case, ISIS, there are jurisdictional obstacles set out in the Rome Statute. Nevertheless, there are still opportunities for criminal liability for human rights violations committed by ISIS against journalists, namely the existence of specific actions and steps from the UN Security Council.